Problems in Learning Uzbek for Asian Language Learners (Journal of Pedagogical Inventions and Practices, 2025)
This study examines the challenges faced by Asian language learners when acquiring Uzbek. It highlights phonetic, grammatical, and lexical difficulties influenced by structural differences between Uzbek and languages such as Chinese, Japanese, and Korean. Key obstacles include Uzbek’s vowel harmony, agglutinative morphology, and case system, which may differ from or partially align with learners' native linguistic structures. Additionally, cultural and sociolinguistic factors, such as exposure to Uzbek and interaction with native speakers, are considered. The findings aim to improve Uzbek language learning methodologies for Asian learners.